1991
DOI: 10.1007/bf02648083
|View full text |Cite
|
Sign up to set email alerts
|

Spelling errors and reading fluency in compensated adult dyslexics

Abstract: Generally, a person who is diagnosed as dyslexic remains diagnosably dyslexic all his/her life. However, occasionally, an individual compensates for his/her difficulties in some way, and by adulthood is no longer diagnosably dyslexic. In what ways are these compensated dyslexics different from both dyslexics and nondyslexics? We compared IQ, achievement test, and spelling error scores in adult dyslexics, adult nondyslexics, and adult compensated dyslexics (N=25) in the two studies reported here. The second stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
1
7

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(167 citation statements)
references
References 13 publications
9
150
1
7
Order By: Relevance
“…For adults with a history of dyslexia, spelling problems persisted through the life span (Bruck, 1993;Lefly & Pennington, 1991), especially in males (Lefly and Pennington, 1991). Connolly et al (2006) found that college students with dyslexia made more spelling errors than a spelling-matched control.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…For adults with a history of dyslexia, spelling problems persisted through the life span (Bruck, 1993;Lefly & Pennington, 1991), especially in males (Lefly and Pennington, 1991). Connolly et al (2006) found that college students with dyslexia made more spelling errors than a spelling-matched control.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…It is one of the most common neurodevelopmental disabilities, affecting [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] 12% of school-aged children across different countries (Peterson and Pennington 2015). Children 22 with dyslexia are slow to learn to read and, even if they attain adequate reading accuracy, they do 23 not read fluently (Lefly and Pennington 1991). Dyslexia appears to be a complex, multi-factorial 24 disorder with a strong genetic component in its aetiology, with heritability estimates from twin Despite extensive investigation, the neuropsychological mechanisms underlying dyslexia are not 1 well understood, and proposals range from deficits specific to the phonological system and subtle 2 problems in sensory perception, to impaired attention and motor deficits (for general reviews, see widely accepted, the specific nature of the deficit is a matter of much debate, as proposals 6 typically only account for a subset of the observed abnormalities -a fact further complicated by a 7 lack of consensus in diagnostic criteria and the highly heterogeneous nature of the disorder 8 (Newbury et al 2014; Bishop 2015).…”
Section: Introductionmentioning
confidence: 99%
“…RWR is an indicator of overall reading ability because it is a multicomponent process involving both lexical orthographic and sublexical phonological processes (Marlow et al, 2001). In some cases, dyslexic individuals can compensate for impairment in singleword reading with experience while still deficient in component phonological skills, but they generally do not reach normal reading ability (Fisher et al, 1999;Lefly and Pennington, 1991). Speed of word recognition as a measure of RWR may be a particularly meaningful measure: in languages such as German and Finnish, which have regular orthographies, low reading speed, rather than low reading accuracy, is a common persistent problem in dyslexia (Landerl, 2001;Leinonen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%